ANALISIS KESANTUNAN BAHASA MEDIA SOSIAL: KOMUNIKASI MAHASISWA KEPADA DOSEN STMIK STIKOM INDONESIA - Agus Ari Iswara; Kadek Yogi Susana (Universitas Warmadewa, 2019)
[Title: Analysis of Language Politeness on Social Media: Communication of Student to Lecturer of STMIK STIKOM Indonesia] In 2018, both student and lecture of STMIK STIKOM Indonesia are more active in communicating and interacting on social media rather than use Short Message Service (SMS). This research aimed to do an analysis about scheme of student utterance politeness, representation use of politeness maxim in their text, and the level of their politeness in interact with their lecture through social media. The data collected from documentation of their conversation on social media in two semesters of 2017 until 2018 and it is also collected from questioner and interview with the lecture as the respondent. The data analyzed by applied some theory. The main theory is the theory of politeness from Leech, continued by theory from Scollon, and then supported by Scale of Likert and Guttman. The Result shows that there are ten (10) schemes of interactions happen between student and lecture. They are (1) about assignment, (2) clarification about study, (3) permit of attendance, (4) confirming about lecture attendance, (5) informing about class schedule, (6) informing their contact, (7) confirming about guidance schedule, (8) additional class schedule, (9) module and learning tools, (10) confirming about test. It is found those politeness maxims used in their utterance are Tact Maxim and Generosity Maxim. The instruments that form their politeness are power, social distance, and weight of imposition. Furthermore, about the politeness level of student utterance based on interview with the lecture, it is found that they uses polite utterance, but most of the lecture said that the collage need to create regulation for controlling student in sending text through social media.